Spunti Italiano elementare 1 - Leisawitz, Daniel; Viale, Daniela (Open textbook library., 2019)
Spunti: Italiano elementare 1 is a unique program for Italian language learning, authored by the Italian faculty of Muhlenberg College (Pennsylvania, USA). Spunti 1 provides fully elaborated course materials for first-semester Italian that college instructors can use and adapt, or students can use on their own. Spunti 1 consists of: 1) an online Pressbook with grammar explanations, cultural material, vocabulary, videos, and self-correcting interactive exercises; 2) printable packets of in-class activities; and 3) complete lesson plans for one semester. Users are free to use Spunti 1 in whole or in part, and are free to adapt it to their needs. Spunti: Italiano elementare 2 and Spunti: Italiano intermedio are the companion texts for second-, third- and fourth-semester Italian, and are still under development.